MOBILE TECHNOLOGIES MANAGEMENT IN THE INFORMATION SPACE OF MODERN INSTITUTE OF HIGHER EDUCATION - Dmitry A. Ivanchenko (Высшее образование в России, 2016)
The paper deals with the prerequisites of application of mobile technologies in institutions of higher education taking into consideration Russian specifics. The author suggeststhe construction of the university informatization strategy, based on using mobile devices; discusses the approaches to mobile devices management in the information space of the university; offers mobile data services to support a variety of organizational and educational processes.